Existence of the solitary traveling waves for a system of nonlinearly coupled oscillators on the 2d -lattice - Bak, S. N. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider a system of differential equations that describes the dynamics of an infinite system of nonlinearly couplednonlinear oscillators on the 2d-lattice. By the method of critical points, we obtain a result on existence of the solitarytraveling waves.